Pensions and the green transition: Policy and political issues at stake - David Natali; Michele Raitano; Giulia Valenti (European Trade Union Institute (ETUI), 2022)
Pension policy has gone through an intense period of reform over the past few decades. However, further changes are likely to take place in the near future. Major global trends, not only population ageing but also globalisation, technological innovation and climate change, are going to shape socio-economic and labour organisation and influence macroeconomic trends and will thus have an impact on the adequacy and long-term sustainability of pension policy. This paper focuses on the challenges of the green transition for pensions. We first examine its possible effects on economic growth and productivity, labour markets and the financial sector. We then investigate the potential consequences of the future ecological transition on the financing of old-age protection, future benefits and their adequacy, and the changing role of trade unions in approaching the complex dilemma of supporting the green transition on the one hand, while defending the short-term interests of their rank and file (in terms of tax, labour market and social policies) on the other.
Keywords: 330